Thermospermine modulates expression of auxin-related genes in Arabidopsis - Tong, Wurina; Yoshimoto, Kaori; Kakehi, Jun-Ichi; Motose, Hiroyasu; Niitsu, Masaru; Takahashi, Taku (Frontiers in Plant Science, 2014)
Thermospermine, a structural isomer of spermine, is widely distributed in the plant kingdom and has been shown to play a role in repressing xylem differentiation by studies of its deficient mutant, acaulis5 (acl5), in Arabidopsis. Our results of microarray and real-time PCR analyses revealed that, in addition to a number of genes involved in xylem differentiation, genes related to auxin signaling were up-regulated in acl5 seedlings. These genes include MONOPTEROS, an auxin response factor gene, which acts as a master switch for auxin-dependent procambium formation, and its target genes. Their expression was reduced by exogenous treatment with thermospermine or by transgenic induction of the ACL5 gene. We examined the effect of synthetic polyamines on the expression of these auxin-related genes and on the vascular phenotype of acl5, and found that tetramines containing the NC3NC3N chain could mimic the effect of thermospermine but longer polyamines containing the same chain had little or no such effect. We also found that thermospermine had an inhibitory effect on lateral root formation in wild-type seedlings and it was mimicked by synthetic tetramines with the NC3NC3N chain. These results suggest the importance of the NC3NC3N chain of thermospermine in its action in modulating auxin signaling.